Estimating currency misalignment using the Penn effect: It is not as simple as it looks. (28th September 2017) - Cheung, Yin‐Wong; Chinn, Menzie; Nong, Xin
Abstract: We investigate the robustness of the Penn effect—the finding that the price level is higher in countries with a higher per capita income—over different samples, measures, and specifications. Testing for the Penn effect has been hampered by the imprecision of the price measures, so that use of different versions of the data set can lead to substantially different results. We find that the price level‐income elasticity is fairly consistently estimated across data sets. However, there is some evidence that the relationship is non‐linear. For developed economies, the quadratic term implies an inverted U‐shaped relationship. Developing economies, on the other hand, display a U‐shaped relationship. Estimates of misalignment differ, depending on the choice of specification and data sets. It appears that the Renminbi (RMB) was fairly valued by 2011. In contrast, the RMB's value was undervalued in 2005, and overvalued in 2014.